Access to finance and its challenge for Micro and Small Scale Enterprise: A case study of Dawuro Zone, Tarcha, Ethiopia - Cherinet Demissie Herano (Universitas Padjadjaran, 2023)
The Main purpose of this study is to examine access to finance and its challenge for Micro and Small Scale Enterprises in the case of Dawuro Zone, Tarcha, Ethiopia. Primary and secondary data were used to conduct the study, and to obtain primary data; the researcher used 257 Micro and Small Enterprises owners and 3 Micro Finance institutions. The sampling technique used for the study was a proportionate stratified sampling technique, and the type of the study was sequential explanatory. Theregression result indicated that the location of operators, the size of Micro and Small Enterprises, the operator's sector, and the operator's financial literacy level have been found to be statistically significant and positively affecting the probability of access to finance for Micro and Small Enterprises while operators age and collateral requirement have negatively and statistically significant with the probability of access to finance for Micro and Small Enterprise. Therefore the study recommended that financial institutions should come up with more flexible, affordable, and attractive requirements in financing micro and small enterprises, and the researcher also advised the owners of Micro and Small Enterprises should have to put clear financial information which will counter problems of information that make Micro and Small Enterprises risky for credit giving institutions